Life‐cycle greenhouse gas emissions reduction potential for corn ethanol refining in the USA. (6th April 2022) - Xu, Hui; Lee, Uisung; Wang, Michael
Abstract: This study evaluates how low‐carbon production technologies applicable to ethanol plants may reduce the life‐cycle greenhouse gas emission (GHG) intensities of corn ethanol production in the USA. Results indicate that options focusing on incremental energy efficiency (e.g., combined heat and power) and yield improvements have a limited impact on GHG reductions. To achieve deep decarbonization (>50% GHG reduction compared to current corn ethanol production), a fuel switch from natural gas (NG) to alternative low‐carbon fuels is needed. Replacing 50% of NG demand at ethanol plants with syngas from biomass through gasification or renewable natural gas from animal waste could achieve significant GHG reductions (11.7–23.5 g CO2 e/MJ ethanol). Adding multiple technologies, including carbon capture and storage, to existing ethanol plants may further reduce GHG emissions to −18.4 g CO2 e MJ −1 ethanol (including land‐use change emissions), which is 120% lower than the carbon intensity of pure gasoline. These results could inform how the ethanol industry could move toward net‐zero ethanol production. © 2022 UChicago Argonne, LLC, Operation of Argonne National Laboratory. Biofuels, Bioproducts and Biorefining published by Society of Industrial Chemistry and John Wiley & Sons Ltd.